Good Corporate Governance and Maqashid Sharia Performance in Southeast Asian Sharia Banking - Yulianto, Mohammad Dedi; Darwanto, Darwanto; Syifaaussakinah, Syifaaussakinah (Al-Tijary, 2023)
Islamic banking has the characteristics of an operation that uses a profit-sharing system, and its main goal is to achieve Falah. This also affects the performance measurement of sharia banking, which also adapts to these two characteristics. One method of measuring the performance of Islamic banking is to use the Maqashid -Based Performance Evaluation Model (MPEM) method. This study aims to prove the effect of good corporate governance variables (board of commissioners, independent commissioners, sharia supervisory board, and audit committee) on the performance of Islamic banking based on the MPEM method. This study uses secondary data obtained from 20 Islamic banks in 4 Southeast Asian countries from 2016 to 2020 observation years. The method used a panel regression model with the random effect as the chosen model. This study found that the board of commissioners and the audit committee have a negative effect on the performance of Islamic banking in Southeast Asia based on Maqashid Sharia. The ratio of the independent commissioners and the sharia supervisory board doesn’t affect the performance of Islamic banking, and the average Maqashid performance index of sharia banking is only around 12.7%. The implication of this study is moreover, to help navigate the Shari‘ah identity through the implementation of an effective Good Corporate Governance (GCG) structure to improve the performance of Islamic banking. On the other hand, increasing the number of members of the board of commissioners doesn't always result in improved performance, thus requiring a more active role from the independent board of commissioners.